Peningkatan Kapasitas Warga RW 02 Kelurahan Pancoran melalui Edukasi dan Pelatihan Pemanfaatan Minyak Jelantah - Fairus, Sirin; Hendriani, Ardina; Purwita, Wiwit (LPkM Universitas Bakrie, 2025)
The Central Statistics Agency (BPS) stated that domestic cooking oil consumption increased by 2.32% per year in the household sector from 2015 to 2020. According to a survey, 95% (n=20) of residents of RW 02, Pancoran Village, South Jakarta are one of the producers of used cooking oil from kitchen activities and 70% do not know how to process used cooking oil into useful products. Used cooking oil that is not managed properly can pollute the environment and is harmful to health if consumed repeatedly. On the other hand, used cooking oil has great potential benefits in various sectors. The purpose of this community service activity is to provide education and training to residents about the management of used cooking oil and how to process used cooking oil waste into useful derivative products containing ecoenzyme. The method used is by distributing questionnaires, education and training in making aromatherapy candles and liquid soap containing ecoenzyme. The indicator of activity achievement is that participants have independently produced aromatherapy candles for a bazaar with better quality. The results of the questionnaire after the training stated that all training participants (100%, n = 14) had understood how to manage used cooking oil properly, had understood how to make used cooking oil derivative products and were interested in making it a business.